2013
DOI: 10.1016/j.peptides.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electroacupuncture Zusanli (ST36) on food intake and expression of POMC and TRPV1 through afferents-medulla pathway in obese prone rats

Abstract: Objective The purpose of this study was to determine the effects of electroacupuncture (EA) ST36 on food intake and body weight in Obese Prone (OP) rats compared to obese resistant (OR) strain on a high fat diet. The influences of EA on mRNA levels of pro-opiomelanocortin (POMC), transient receptor potential vanilloid type-1 (TRPV1), and neuronal nitric oxide synthase (nNOS) were also examined in the medulla regions and ST36 skin tissue. Methods Advanced EA ST36 was conducted in two sessions of 20 min separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 47 publications
(95 reference statements)
5
22
0
Order By: Relevance
“…Han et al reported inhibitory effects of EA at ST36 on food intake and body weight in both regular and DIO rats [15,16]. Similar findings were reported by Ji et al in obesity-prone rats [17]. To the best of our knowledge, the proposed CEA is the first method to treat obesity via chronically implanted electrodes at acupoints.…”
Section: Discussionsupporting
confidence: 57%
“…Han et al reported inhibitory effects of EA at ST36 on food intake and body weight in both regular and DIO rats [15,16]. Similar findings were reported by Ji et al in obesity-prone rats [17]. To the best of our knowledge, the proposed CEA is the first method to treat obesity via chronically implanted electrodes at acupoints.…”
Section: Discussionsupporting
confidence: 57%
“…However, a few reports showed that EA ST36 may enhanced appetite to a certain extent [ 63 ], but more studies suggested that EA ST36 significantly inhibited feeding and body weight gain [ 64 69 ]. The possible mechanisms are down-regulated orexigenic peptides, such as neuropeptide Y (NPY) [ 64 ], upregulates anorexigenic hormones, including proopiomelanocortin (POMC) [ 65 ], α-Melanocyte-stimulating hormone (α-MSH) [ 66 ], and cholecystokinin (CCK) [ 67 69 ]. Nevertheless, there are other acupoints used for the treatment of obesity, further studies should test whether stimulation of other acupoints acts through a similar mechanism like stimulation of ST36 and ST25.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent evidence, acupuncture at ST 36 can regulate gastric activity, depending on the neural basis or structure and is probably related to the central neurons in the dorsal vagal complex [33]. EA-induced expression of transient receptor potential vanilloid type-1 neuronal nitric oxide synthase (TRPV1-nNOS) and the NTS/gracile nucleus is involved in the signal transduction of EA stimuli via somatosensory afferent-medulla pathways [34]. In our study, the modes of response to EA at ST36 were more complicated in gastric-related neurons of the NTS than in those of the SDH.…”
Section: Discussionmentioning
confidence: 99%